2022
DOI: 10.1186/s12610-022-00162-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of Fournier’s gangrene during the Covid-19 pandemic era: make a virtue out of necessity

Abstract: Background Fournier’s gangrene (FG) is a necrotizing fasciitis caused by aerobic and anaerobic bacterial infection that involves genitalia and perineum. Males, in their 60 s, are more affected with 1.6 new cases/100.000/year. Main risk factors are diabetes, malignancy, inflammatory bowel disease. FG is a potentially lethal disease with a rapid and progressive involvement of subcutaneous and fascial plane. A multimodal approach with surgical debridement, antibiotic therapy, intensive support car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 198 publications
0
4
0
Order By: Relevance
“…Furthermore, it was reported that fear of transmission during the coronavirus pandemic had a positive correlation with the stress level of urological patients [28]. Occasionally, treatment methods are limited because of concerns regarding infection, and measures have been reported [29]. This study was conducted during the SARS-CoV-2 era and was able to show a correlation between anxiety and depression in urological cancers, one of the major problems in the urology sector that can affect outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, it was reported that fear of transmission during the coronavirus pandemic had a positive correlation with the stress level of urological patients [28]. Occasionally, treatment methods are limited because of concerns regarding infection, and measures have been reported [29]. This study was conducted during the SARS-CoV-2 era and was able to show a correlation between anxiety and depression in urological cancers, one of the major problems in the urology sector that can affect outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…At present, it is believed that only approximately one-quarter of cases are idiopathic diseases with unknown causes, and more than 75% have definite aetiologies ( 26 , 27 ). As for the infection site, 30%–50% originate from the rectum and anus, 20%–40% originate from the urogenital system, and 20% originate from skin infection ( 28 ). Why is there only “genitalia” but no “perianal” or “perineum” in the top 20 burst words?…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic bacteria and anaerobic bacteria exist at the same time in patients with FG. When the host has immunodeficiency, a polymicrobial flora are usually involved with a synergic mechanism of aggressiveness ( 28 ). It was reported 54% of case were caused by Polymicrobial infection ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fournier’s gangrene is particularly severe and historically can have mortalities up to 20%–80% reported in the literature 16. This has decreased to 10%–20% due to modern, multidisciplinary management consisting of early and aggressive surgical debridement, broad spectrum antibiotic coverage and fluid resuscitation 17 18…”
Section: Discussionmentioning
confidence: 99%